(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Water pollution by the discharge of dye residue has been polluting the planet for decades. Chitosan is one of the natural abundant biomasses that show excellent adsorption toward colorants. Nevertheless, sophisticated chemical modifications of chitosan are inevitable to enhance physical and chemical stabilities in practical applications. In the present study, simple freeze-drying has been adopted to chitosan (CHI) beads showing good stability at low levels of pH. The results show complete decolourisation of Reactive Blue 19 (RB19) within 2 hours at pH 3 and temperature of 37 00b0C. The encapsulation of live bacterium Lactobacillus casei (L. casei) into chitosan beads for dyestuff removal is also evaluated. Kinetics studies show a faster initial rate of adsorption by L. casei-chitosan beads at pH 3 and temperature of 37 00b0C. The adsorptions partially follow the intraparticle diffusion mechanism.